Development of a Method for a Sensitive Simultaneous Determination of Dopamine and Paracetamol in Biological Samples and Pharmaceutical Preparations - Ali Babaei; Aliyeh Dehdashti; Mohammad Afrasiabi (International Journal of Electrochemistry)
A chemically modified electrode is constructed based on multiwalled carbon nanotube—modified glassy carbon electrode (MWCNTs/GCE). The measurements were carried out by application of differential pulse voltammetry (DPV), cyclic voltammetry (CV), and chronoamperometry (CA) methods. Application of DPV method showed wide linear range of DA from 1 μM to 540 μM and a detection limit of 0.098 μM (S/N=3). The linear range of PAR of 3 μM to 300 μM and a detection limit of 0.15 μM, were obtained. The modified electrode showed electrochemical responses with high sensitivity, high selectivity, and excellent stability for DA and PAR determination at optimal conditions, which makes it a suitable sensor for simultaneous submicromolar detection of DA and PAR in solutions. The analytical performance of this sensor has been evaluated for detection of DA and PAR in human serum, human urine, and pharmaceutical preparation with satisfactory results.